Factors Affecting the Implementation of Hospital Information System (HIS) - Br Ginting, Setyawati; Felix Kasim; Rahmad Ramadhan Ritonga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The implementation of the Hospital Management Information System (SIMRS) at the Regional Public Hospital of Sidikalang (RSUD Sidikalang) aims to enhance the efficiency and quality of healthcare services. However, technical challenges such as the lack of data integration across units and the readiness of human resources (HR) hinder the success of its implementation. Research Objectives: This study aims to analyze the implementation conditions of SIMRS at RSUD Sidikalang, identify the factors that hinder its success, and provide policy recommendations to improve the system’s efficiency, focusing on HR readiness, technological infrastructure, and hospital management support. Research Methodology: This research uses a quantitative approach with a descriptive correlational design. Data was collected through surveys distributed to 161 employees of RSUD Sidikalang involved in the management of SIMRS. Data analysis was performed using the Chi-Square test to determine the relationship between variables, and multiple logistic regression to analyze the factors most affecting SIMRS implementation. Research Results: The findings indicate that the Human Resources (HR) factor has a significant impact on the success of SIMRS implementation. Respondents who rated HR positively were more likely to assess SIMRS implementation as good. Technology and organizational factors also played a crucial role in enhancing the effectiveness of SIMRS. Conclusion: The success of SIMRS implementation at RSUD Sidikalang heavily depends on HR readiness, the quality of technological infrastructure, and hospital management support. Continuous HR training, adequate technology maintenance, and improved coordination between hospital units are key to maximizing the benefits of SIMRS.